2019
DOI: 10.1177/0143034319830452
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal influences of depressive moods on problematic mobile phone use and negative school outcomes among Korean adolescents

Abstract: The study aimed to examine the longitudinal causal relationships of depressive moods, problematic mobile phone use, and negative school outcomes based on the cognitive-behavioral model among Korean adolescents. The changes within each construct over time were also explored. A total of 1,610 valid responses from three-year longitudinal data from the Korean Children and Youth Panel Survey were analysed and multivariate latent growth modeling was used. Depressive moods, problematic mobile phone use, and negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Negative emotion is an emotional state that individuals often experience in their daily life. Some theories and a large quantity of empirical evidence have suggested that negative emotion is a key trigger for PMPU (Augner & Hacker, 2012; Billieux, 2012; Choi et al., 2015; De‐Sola et al., 2017; Elhai, Dvorak, et al., 2017; Elhai, Levine, Alghraibeh, et al., 2018; Hong et al., 2012; Hussain et al., 2017; Jun, 2019; Matar Boumosleh & Jaalouk, 2017; Smetaniuk, 2014). Lately, there is a growing body of literature recognising that identifying the underlying mechanism is important for exploring the influence of negative emotion on PMPU (Elhai, Levine, et al., 2017; Elhai, Levine, O’Brien, et al., 2018; Elhai, Tiamiyu, et al., 2018; Elhai, Vasquez, et al., 2018; Kim et al., 2015).…”
Section: Negative Emotion and Pmpumentioning
confidence: 99%
“…Negative emotion is an emotional state that individuals often experience in their daily life. Some theories and a large quantity of empirical evidence have suggested that negative emotion is a key trigger for PMPU (Augner & Hacker, 2012; Billieux, 2012; Choi et al., 2015; De‐Sola et al., 2017; Elhai, Dvorak, et al., 2017; Elhai, Levine, Alghraibeh, et al., 2018; Hong et al., 2012; Hussain et al., 2017; Jun, 2019; Matar Boumosleh & Jaalouk, 2017; Smetaniuk, 2014). Lately, there is a growing body of literature recognising that identifying the underlying mechanism is important for exploring the influence of negative emotion on PMPU (Elhai, Levine, et al., 2017; Elhai, Levine, O’Brien, et al., 2018; Elhai, Tiamiyu, et al., 2018; Elhai, Vasquez, et al., 2018; Kim et al., 2015).…”
Section: Negative Emotion and Pmpumentioning
confidence: 99%
“…According to Jun (2019), nearly all adolescents aged 12-19 in Korea own a mobile phone and most of them (97%) are smart phones. According to Pew Research Center, 95 % of Americans own a mobile phone of some kind and in Uganda, the percentage of phone ownership is only at 65%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have evidenced a relationship between academic achievement and nomophobia behaviour [49] of higher education students. Several authors acknowledge that low academic productivity and achievement are associated with nomophobia [50][51][52][53][54][55]. Additionally, smartphone dependency negatively influences students' involvement in practical activity, focus on studies and ultimately, academic performance [31].…”
Section: Introductionmentioning
confidence: 99%